REPRODUCTIVE STRATEGIES IN ENDANGERED AMPHIBIANS: CHALLENGES AND OPPORTUNITIES - Sheikh Zuhaib (PT. Radja Intercontinental Publishing, 2024)
Amphibians are among the most threatened vertebrates, with over 40% of species facing extinction. Their reproductive strategies, ranging from oviparity to viviparity and complex parental care behaviours, are highly specialised and adapted to specific ecological conditions. However, these strategies are increasingly jeopardised by habitat destruction, climate change, pollution, invasive species, and diseases like chytridiomycosis. This article explores the reproductive adaptations of endangered amphibians, highlighting the challenges to their survival and the opportunities for conservation. Conservation efforts such as habitat restoration, ex-situ breeding programmes, assisted reproduction technologies, and community involvement offer hope for reversing population declines. Case studies, including the success of Axolotl conservation and the failure to save the Golden Toad, emphasise the need for integrated approaches to tackle multifaceted threats. By addressing reproductive ecology and implementing innovative solutions, we can safeguard amphibian biodiversity and their ecological roles for future generations.